Development of worker ovaries in Brazilian Africanized honeybees (Hymenoptera: Apidae) - Patricio, Karina [UNESP]; Cruz-Landim, Carminda da [UNESP] (My University, 2004)
The present paper compares the worker ovaries development in queen right and orphaned colonies of Brazilian Africanized honeybee. The results show that in both colonies some workers starting 20 days after emergence, present some kind of ovary development. As the workers from queen right colony get older the degree of the ovary development increases. Vitellogenesis in worker ovaries may occur in queen right and orphaned colonies, but its frequency is lower in queen right colonies.
Keywords: Orphaned colonies; Ovary development; Queen; Vitellogenesis; Worker; Apidae; Apis mellifera; Hymenoptera; Invertebrata